Study of animal welfare status in dairy cow herds in Hungary – looking for causes of lameness - Gudaj, Richard; Komlósi, István; Brydl, Endre (Acta Agraria Debreceniensis, 2012)
In the last 20–30 years lameness in cattle was found to be third the most influential disease next to mastitis and reproduction disorders. Studies have been established to explore reasons for lameness and prevention. The problem with more robust prevention plans is that knowledge and research evidence is not strong enough to run an effective prevention plan. The aim of the research is to look for reasons of lameness by observing number of cows on 6 farms during 2 lactations. Performance data will be put together to body condition score (BCS) and lameness scores. Other examination is focused on monitoring of 40 farms. This part of the project is more related to extension, collecting and sharing solutions for decreasing lameness. Producers are advised what kind of measures are possible to reduce occurrence of lameness. Effectiveness of those actions will be measured at the end of the study. The first preliminary results show lack in almost all preventive measures needed to be taken in minimising lameness. Those areas are related to poor facilities, lack of straw, problems with labour and basic management.